Social Justice Under Perspective of Philosophy of Law and Maqâsid Al-Sharî‘Ah - Sanuri Sanuri (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2012)
Justice in the philosophy of law becomes a core which must be met through the existing law. Aristotle asserted that justice as the core of the legal philosophy can be understood in terms of numerical equality and equality of proportion. He also distinguished the type of justice into distributive justice and corrective justice. Meanwhile, John Rawls asserted that the enforcement of justice has a social dimension or well-known with social and reciprocal benefits. In Islam, justice is discussed as a matter of theology of divine justice that later emerged the two schools of thought; Mu‘tazilah and Ash‘arîyah. In addition, the theory of justice is also a fundamental theme in the philosophy of Islamic law, particularly in the discussion of maqâsid al-sharî‘ah which asserts that Islamic law is regulated to create and protect the social benefits to mankind. The theory of social benefit was initially introduced by Imam al-Haramayn al-Juwaynî then developed by his student, al-Ghazâlî. The next Islamic legal theorist that specifically discussed about maqâsid al-sharî‘ah was ‘Izz al-Dîn b. ‘Abd. al-Salâm of Shafi‘îah. And the discussion about maqâsid al-sharî‘ah in a systematic and clear way was carried out by al-Shâtibî of Malikîyah in his book al-Muwâfaqât. In addition, al-Tûfî also provides radical and liberal views about the theory of social benefit. Justice in the philosophy of law becomes a core which must be met through the existing law. Aristotle asserted that justice as the core of the legal philosophy can be understood in terms of numerical equality and equality of proportion. He also distinguished the type of justice into distributive justice and corrective justice. Meanwhile, John Rawls asserted that the enforcement of justice has a social dimension or well-known with social and reciprocal benefits. In Islam, justice is discussed as a matter of theology of divine justice that later emerged the two schools of thought; Mu‘tazilah and Ash‘arîyah. In addition, the theory of justice is also a fundamental theme in the philosophy of Islamic law, particularly in the discussion of maqâsid al-sharî‘ah which asserts that Islamic law is regulated to create and protect the social benefits to mankind. The theory of social benefit was initially introduced by Imam al-H{aramayn al-Juwaynî then developed by his student, al-Ghazâlî. The next Islamic legal theorist that specifically discussed about maqâsid al-sharî‘ah was ‘Izz al-Dîn b. ‘Abd. al-Salâm of Shafi‘îah. And the discussion about maqâsid al-sharî‘ah in a systematic and clear way was carried out by al-Shâtibî of Malikîyah in his book al-Muwâfaqât. In addition, al-T{ûfî also provides radical and liberal views about the theory of social benefit. Keywords:Social justice, philosophy, Islamic law, maqâsid al-sharî‘ah.